Synthetic food dyes in electronic cigarettes. (January 2019) - Korzun, Tetiana; Munhenzva, Ian; Escobedo, Jorge O.; Strongin, Robert M.
Abstract: Apart from nicotine, the identity and levels of the ingredients of electronic cigarette liquids are typically not available to consumers. Herein we have identified and quantified synthetic dye additives used in e-liquids. Tartrazine, Brilliant Blue FCF and Allura Red AC were found in six randomly-chosen commercial e-liquids. They were present in amounts comparable to those of dye concentrations in colored foodstuffs. The synthetic dyes found in the e-liquids are generally recognized as safe for ingestion; however, their inhalation toxicity is unknown. The ongoing treatment of e-liquids as foodstuff, for example via the use of ingredients such as sweeteners, synthetic dyes and related non-volatile additives, may increase appeal as well as potential harm without directly enhancing intended medicinal benefits. Graphical abstract: Image 1 Highlights: Commercial colored e-liquids contain food colorants at levels similar to foodstuffs. E-liquid formulations include dyes that are intended for ingestion, not inhalation. A simple protocol can be used for the analysis of synthetic food dyes in e-liquids.